If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y=2(3-y)+15
We move all terms to the left:
y-(2(3-y)+15)=0
We add all the numbers together, and all the variables
y-(2(-1y+3)+15)=0
We calculate terms in parentheses: -(2(-1y+3)+15), so:We get rid of parentheses
2(-1y+3)+15
We multiply parentheses
-2y+6+15
We add all the numbers together, and all the variables
-2y+21
Back to the equation:
-(-2y+21)
y+2y-21=0
We add all the numbers together, and all the variables
3y-21=0
We move all terms containing y to the left, all other terms to the right
3y=21
y=21/3
y=7
| -7+3p=p+5 | | 4x2-x+16+3x=7x-12-5x | | x+45+3x3=180 | | i/4+5=93 | | .1(x+111)=-2(3-x) | | y/3+y/6=5/3 | | 180=6x+4 | | 28+102+7x+16=180 | | 18=-2(x-2)+4x | | 28+x=2 | | 18x-3.8x=7.36x-1.9x | | 7x=24+3x= | | 9x-25+6x=6x+3x+10+7 | | 6(x-4)+3=-21 | | 3/8x=2=14 | | -4w+3{2w-1}=17 | | 8m+20=400 | | 9a-11=28 | | X-92=7(2x+3)-9 | | 3(4q+1)=-21 | | 71-y=284 | | 3x+22+5x-13+4x+24=180 | | 8m+20=440 | | 3(2m-4)/6+5=8 | | -2(4x-4)-3x+5=-90 | | 2x+25=3x-21 | | 241=72-x | | -3(x+2)+15=14-4x | | (-x)+(-3)=-13 | | -10x+(-15)x+16=17+15 | | 11-n=-20 | | 2(3x-2)+5=-6(4-x)+25 |